US research needs related to fatigue, sleep, and working hours among oil and gas extraction workers. Issue 11 (14th November 2021) - Hagan‐Haynes, Kyla; Pratt, Stephanie; Lerman, Steven; Wong, Imelda; Baker, Angela; Flower, David; Riethmeister, Vanessa
Abstract: Background: During 2003–2013, 1189 US oil and gas extraction (OGE) workers died while working, resulting in an average annual workplace fatality rate seven times that for all US workers. OGE work commonly involves long hours, shiftwork, irregular schedules, and long commutes, but effects of these factors on fatigue, occupational injury, and illness in OGE are largely unknown. Methods: A scoping review of relevant OGE research during 2000–2019 was completed and supplemented by input from a NIOSH‐sponsored Forum. Results: Seventy‐eight papers were identified; 76% reported only offshore research. Five themes for research needs emerged: build knowledge about the impacts of fatigue; explore interactions between on‐ and off‐the‐job risk factors; identify and evaluate interventions; assess effectiveness of technology; and increase the diffusion of fatigue risk management information. Conclusions: Further collaboration between researchers and OGE operators and contractors can lead to action‐oriented recommendations to mitigate the effects of fatigue, inadequate sleep, and shiftwork.